Exploring the ring-opening metathesis polymerization process by kinetic Monte Carlo simulation - Ákos Szabó; Béla Iván; Ervin Kovács (Chemical Engineering Journal Advances)
Investigating the kinetics of polymerization reactions is a powerful tool to obtain information for the engineering design of such processes. It provides insights into how the relative rates of elementary reactions which influence both the kinetics of the reactions and thus characteristics of the products as well, particularly when the reaction parameters of these reactions are unknown. Among polymerization processes, ring-opening metathesis polymerization (ROMP) has gained broad academic and industrial interest, due to its mild conditions to obtain a wide range of polymer products. In this study, kinetic Monte Carlo simulation was applied to reveal the effect of the elementary reactions of ROMP on the kinetics and product distribution. Both the propagation and the cross-metathesis reactions were considered, with the latter leading to the formation of various types of macrospecies whose population levels were also monitored. Relevant tendencies were observed regarding how the variations in the reaction parameters of the elementary reactions of this polymerization process, such as reaction probabilities, monomer addition method, catalyst-to-monomer ratio, and reaction time, affect the kinetics of the polymerization process and the product distributions. These variations also influence the key macromolecular parameters of the resulting polymeric materials, including chain length distribution (CLD), population levels, and polymer functionalities. The results of this study indicate that this simulation technique is a valuable tool for mapping the tailoring possibilities of modifying the reaction parameters of ROMP to achieve desired properties. These properties include number average molecular weight, polydispersity, chain end functionality, and macrocycle-free products.